A Comparative Study of Safer Electrical Systems in Developing Countries-Quantitative Approach in Egypt and Iraq - Kassem, Hassan; Bishtawi, Tariq Yousef (Journal of engineering sciences and information technology, 2025)
This study presents a comparative quantitative analysis of electrical safety systems in developing countries, using Egypt and Iraq as case studies. The objective was to evaluate critical factors influencing electrical safety and identify areas for improvement by comparing practices with those in industrialized nations. Structured questionnaires were distributed to 156 chartered engineers, certified electricians, and lecturers, of which 122 valid responses were collected (response rate = 78.2%). The survey measured the perceived significance of five variables—installation codes and standards, product standards and economic factors, inspection and testing enforcement, risk attitude and cultural factors, and educational and training factors-using a 5-point Likert scale. Statistical analyses, including Chi-square (χ² = 525.75, p < 0.001) and ANOVA (F = 261.02, p < 0.001), confirmed significant differences in importance among factors. Educational and training aspects received the highest rating (91.8% “very important”), whereas risk attitude and cultural factors ranked lowest (6.6%). Reliability analysis yielded a Cronbach’s α of 0.76, indicating moderate internal consistency. Additional data from 42 lecturers identified deficiencies in training units on “Inspecting, Testing, and Commissioning” (17%) and “Ensuring Safe Site Working” (22%). The findings underscore that enhancing vocational education, revising inspection frameworks, and enforcing safety codes are pivotal for reducing electrical hazards. The study recommends reforming technical training curricula, strengthening enforcement capacity, and promoting intersectoral collaboration to achieve sustainable safety improvements in developing contexts.